Relationships in Eighteenth-Century Ballads – Negotiation, Ideology, Imagination - Atkinson, David (Tautosakos darbai, 2020)
The eighteenth century in England is not well represented in the standard ballad editions, but there were many printed ballads presenting a wide range of human relationships, marital and familial, romantic and sexual. Scholars have argued variously that such ballads enabled the negotiation of real-life relationships, that they embodied the prevailing patriarchal ideology of the time, and that they allowed their audience to imagine situations outside of their everyday experience. Ballads depicting several different sorts of relationships are described here. While song texts do describe social relationships, they do so in a way that means real social relationships should not be read back from them in isolation from the external data.
Keywords: ballads; 18th century; relationships; ideology; imagination